2018
DOI: 10.1155/2018/1742529
|View full text |Cite
|
Sign up to set email alerts
|

A Predictable Aesthetic Rehabilitation of Deciduous Anterior Teeth in Early Childhood Caries

Abstract: Aesthetic dentistry plays a significant role not only in adults but also in pediatric patients. However, a pediatric dentist is faced with the dual problem of satisfying the aesthetic expectations of the patient and parents as well as managing the pediatric patient. In the present era, there are numerous restorative techniques that can be applied to different clinical scenarios. However, we have to choose the technique that best suits our patient, not only biologically but also aesthetically, psychologically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Small crown size, caries pattern, and the behavior of the patient plays a big role in successful treatment for restoring the esthetic appearance for young patients. Destructed anterior primary teeth with root canal treatment need a retentive post to hold the coronal crown on the treated canal [ 1 , 2 , 12 , 13 ]. However, post selection is not an easy or successful procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Small crown size, caries pattern, and the behavior of the patient plays a big role in successful treatment for restoring the esthetic appearance for young patients. Destructed anterior primary teeth with root canal treatment need a retentive post to hold the coronal crown on the treated canal [ 1 , 2 , 12 , 13 ]. However, post selection is not an easy or successful procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A glass fiber post is one of the posts used in some cases of primary anterior teeth [ 2 , 13 ]. With root canal treatment and coronal placements, it can be used as an alternative to other post types for root canals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, only a few systematic reviews on dental caries have been reported among Indian population. [ 17 18 19 20 ] However, each study has its own limitations such as the use of a limited number of articles, extraction of published reports from few electronic databases, lack of complete analysis, or unavailability of recently published articles. Few systematic reviews have focused on only children or the elder population.…”
Section: Introductionmentioning
confidence: 99%